2022
DOI: 10.1017/s0144686x2200023x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional poverty index: a multilevel analysis of deprivation among Iranian older adults

Abstract: Although the older adult population faces a higher risk of poverty compared to others, there is no clear picture of their poverty in Iran. The aim of this study was to measure multidimensional poverty and its related factors among Iranian older adults. This cross-sectional study was conducted from July to November 2019 and collected data by interviewing 1,280 participants in Tehran, Iran. To compute multidimensional poverty, four dimensions were used: health (disabilities), education, housing and standard of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A similar relationship for older women being poorer than older men was established in Iran. 23 Using the same methods in this study, we demonstrated that older women in South Africa were more at risk for dementia. 38 Being a widow, separated or divorced was a risk factor for dementia.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A similar relationship for older women being poorer than older men was established in Iran. 23 Using the same methods in this study, we demonstrated that older women in South Africa were more at risk for dementia. 38 Being a widow, separated or divorced was a risk factor for dementia.…”
Section: Discussionmentioning
confidence: 51%
“…A 2021 United Nations Development Program (UNDP) study projected that 97% of Afghans will be poor in 2022 following a contraction of the GDP estimated at 13.2%. 18 Older adults are particularly at risk of multidimensional poverty as evidenced in Afghanistan, 19 the United States, 20 Hong Kong, 21 , 22 Iran, 23 and Taiwan. 24 Estimates from a mental health study (n = 4336) established dementia prevalence at 5.8% for Afghans over age 65.…”
Section: Introductionmentioning
confidence: 99%
“…When c i ≥ k, individual i is defined as multidimensionally poor and c i (k) = c i ; otherwise c i (k) = 0. M 0 has good decomposability, which can be decomposable by subpopulations or indicators (Alkire and Santos, 2014;Kamal et al, 2022).…”
Section: Measurementmentioning
confidence: 99%
“…Some related studies using cross-sectional data pointed out that the ageing of physical function and the weakening of labour ability are the reasons that make older adults more vulnerable to poverty. Thus, social security, work, and income are essential for older people to cope with poverty risks and maintain welfare (Zhang and Yang, 2020;Amarante and Colacce, 2022;Kamal et al, 2022). Therefore, in this study, we included education, health, living standards, social security, work, and income as the five dimensions of multidimensional poverty on 14 indicators (Table 1).…”
Section: Dimensions Indicators and Weights Of Mpimentioning
confidence: 99%
See 1 more Smart Citation